(untitled) (Research, Society and Development, 2022)
Use biological or synthetic scaffolds to conduct cellular events of the regenerative process constitute one of the major strategies in regenerative medicine area. Customized scaffolds built by additive manufacturing prove to be a great solution to this problem. Two desired features that aid in scaffold’s biocompatibility are the surface roughness and the geometric characteristic of the topography, usually achieved by a chemical procedure performed after printing. This research presented a modification on a 3D printer nozzle for directly generating an external topography in the extruded filaments, eliminating the need for an additional post-processing step. Cell morphology and viability on supports printed by the proposed and conventional method were evaluated in in vitro experiments and the new nozzle proved to be efficient in generating printed filaments with a degree of cytocompatibility superior to those obtained by conventional filaments.